2019
DOI: 10.1101/698019
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution and restoration of serotonin-immunoreactive paraneuronal cells during caudal fin regeneration in zebrafish

Abstract: Aquatic vertebrates possess diverse types of sensory cells in their skin to detect stimuli in the water. In the adult zebrafish, a common model organism, the presence of such cells in fins has only rarely been studied. Here, we identified scattered serotonin (5-HT)-positive cells in the epidermis of the caudal fin. These cells were distinct from keratinocytes as revealed by their low immunoreactivity for cytokeratin and desmosome markers. Instead, they were detected by Calretinin (Calbindin-2) and Synaptic ves… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Whether this inverse architecture might affect hydrodynamic properties that regulate ray bifurcation requires further interdisciplinary studies. Indeed, our collaborative projects have previously suggested that fluid dynamics might provide cues for the ray-interray distribution of sensory cells and for the position of ray bifurcations in the regenerating zebrafish fin (Puri et al, 2017;König et al, 2019;Dagenais et al, 2021). In agreement with the hypothesis of the extrinsic input for ray morphogenesis, our experiments with ray excision triggered a distal shift of ray branchpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this inverse architecture might affect hydrodynamic properties that regulate ray bifurcation requires further interdisciplinary studies. Indeed, our collaborative projects have previously suggested that fluid dynamics might provide cues for the ray-interray distribution of sensory cells and for the position of ray bifurcations in the regenerating zebrafish fin (Puri et al, 2017;König et al, 2019;Dagenais et al, 2021). In agreement with the hypothesis of the extrinsic input for ray morphogenesis, our experiments with ray excision triggered a distal shift of ray branchpoints.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a monolayer of bone-depositing osteoblasts covers each hemiray; an artery runs through the middle of each ray, while veins flank the dorsal and ventral margins of each ray (Xu et al, 2014); and previous analyses of cell lineages within the caudal fin identified pigment cells, fibroblasts, and neural crest-derived Schwann cells running through the rays (Lee et al, 2013;Tu and Johnson, 2011). Additionally, staining of fins with general axonal markers indicates axons innervate the adult fin (König et al, 2019;Lisse et al, 2016;Lee et al, 2013). However, the identity of these axons and the relationship between nerves and other anatomical structures in the caudal fin remains poorly described.…”
Section: Adult Peripheral Axons Innervate Each Bony Ray Of the Caudal Finmentioning
confidence: 99%
“…Samples were blocked in 5% goat serum in PBST (PBS + 0.3% Triton) for at least 1 h at room temperature prior to antibody staining (König et al, 2019), then incubated in primary antibody diluted in PBST overnight at 4°C. The following day, following 4x15 min washes in PBST, samples were incubated with the appropriate secondary antibody diluted in PBST overnight at 4°C.…”
Section: Whole Mount Stainingmentioning
confidence: 99%